Yusuf Khos Hajib's Concept of Social Development - Asadovich, Muhamedov Asror (Indonesian Journal Publisher, 2024)
This article explores the philosophical views and social concepts of Yusuf Has Hajib, a significant thinker from the medieval period, whose ideas remain relevant to addressing contemporary societal challenges. His socio-philosophical framework centred on harmony, compromise, and solidarity, offering timeless solutions for political, economic, and social issues. By analysing Hajib's ideas, this study connects his philosophy with modern debates on governance, human dignity, and social justice. Yusuf's emphasis on fairness, the role of leaders, and the need for mutual respect across social strata highlights his forward-thinking approach. His work, particularly Kutadgu Bilig, offers insights into creating an ideal society based on justice and humanity. Furthermore, the research draws parallels between Hajib's thoughts and modern legal, political, and religious discussions in Uzbekistan, illustrating the enduring influence of his wisdom in fostering unity, addressing social inequality, and shaping the national ethos. The article underscores the relevance of philosophical heritage in contemporary reforms and policies, particularly in advancing human dignity, governance, and social harmony.